Is CAPM Still Valid in Today’s Market Scenario? - Rabha, Debajit; Singh, Rajkumar Giridhari (Indian Journal of Finance, 2022)
The current study examined the CAPM’s applicability in the Indian capital market. The study collected weekly closing price data of 48 companies listed on the NSE Nifty 50 index for 10 years, from April 2011 to March 2021. The five portfolios were formed by taking 10 stocks for each portfolio except the last portfolio, which had eight stocks starting from the highest beta securities to the lowest beta security. Rolling regression methodology was applied where the sample data was divided into 3 years, which kept moving for a quarter. A constrained model proposed by Bajpai and Sharma (2015) was tested, and a comparison was made between the constrained model and the conventional model. In the Indian capital market, CAPM is found to be very important, and the constrained model in this study outperformed the conventional model.